1996
DOI: 10.1111/j.1349-7006.1996.tb03160.x
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Trial of the Preventive Effect of Pre‐operative Transcatheter Arterial Embolization against Recurrence of Hepatocellular Carcinoma

Abstract: To clarify whether pre‐operalive transcatheter arterial embolization (TAE) improves survival after hepatectomy, a prospective randomized comparative study was done. Of a total of 115 registered patients having solitary hepatocellular carcinoma (HCC) 2 to 5 cm in diameter, 18 (15.7%) were excluded after randomization. As a result, 97 patients were chosen as subjects and divided into two groups: hepatectomy with (group A: n = 50) and without (group B: n=47) pre‐operative TAE. The period of observation of the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
121
3
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(135 citation statements)
references
References 14 publications
9
121
3
2
Order By: Relevance
“…The use of cTACE prior to resection of HCC has been examined in 3 RCTs, universally yielding negative results in terms of OS and DFS (47)(48)(49). One such study, published by Zhou et al (47) delineated the negative impact of preoperative cTACE on a range of parameters including post-cTACE complications, impairment of liver function and increased technical difficulty for future transarterial treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The use of cTACE prior to resection of HCC has been examined in 3 RCTs, universally yielding negative results in terms of OS and DFS (47)(48)(49). One such study, published by Zhou et al (47) delineated the negative impact of preoperative cTACE on a range of parameters including post-cTACE complications, impairment of liver function and increased technical difficulty for future transarterial treatments.…”
Section: Discussionmentioning
confidence: 99%
“…27,209 Chemoembolization of the tumor prior to resection offers no benefit. 210 The same is true for the general use of portal vein embolization of the hepatic lobe hosting the tumor 211,212 to induce compensatory liver growth and functional capacity in the non-affected lobe prior to a major resection. It has also been suggested that malignant hepatocytes may also respond to the proliferative stimulus and this could result in uncontrolled tumor progression.…”
Section: Surgical Resectionmentioning
confidence: 99%
“…19,20 One was a multicenter, randomized, controlled trial conducted in Japan that examined the effects of preoperative TAE without any chemotherapeutic agents in patients with HCC who had 20 If the purpose of preoperative TAE (or TACE) is to prevent tumor spread arising from intrahepatic micrometastases that are present at the time of hepatectomy or from intraoperative manipulation, then it is not beneficial to perform preoperative TAE (or TACE) uniformly, regardless of whether patients have intrahepatic micrometastases. However, it may be possible to demonstrate the efficacy of preoperative TAE (or TACE) if the procedure is undergone by patients who have intrahepatic micrometastases or the possibility of intraoperative tumor spread.…”
Section: Discussionmentioning
confidence: 99%